2010
DOI: 10.4314/as.v9i1.57448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sprouting and pre-gelatinization on the physicochemical properties of sorghum-pigeon pea composite blend used for the production of breakfast cereal.

Abstract: Sprouted (96-hour) and pregelatinized (78 0 C) sorghum grains were milled and blended with graded proportion of pigeon-pea and used in formulating flaked breakfast cereal. A commercial ready-to-serve breakfast cereal served as product control. The flour blends and formulated products were subjected to the physicochemical quality analyses using standard methods. Results of the amylose content of the pregelatinized sample showed higher (p<0.05) amylose content than the sprouted samples. The sorghum samples used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The method of Mbaeyi and Onweluzo () was used in analyzing minerals. Mineral analysis of samples taken from the fermenting maize‐pigeon pea ogi at 24‐hr interval was determined in three phases: sample preparation, sample digestion, and atomic absorption spectrophotometer (AAS) analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of Mbaeyi and Onweluzo () was used in analyzing minerals. Mineral analysis of samples taken from the fermenting maize‐pigeon pea ogi at 24‐hr interval was determined in three phases: sample preparation, sample digestion, and atomic absorption spectrophotometer (AAS) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Fortification of food refers to the addition of essential micronutrients to food particularly added to correct specific nutritional deficiencies such as addition of vitamins and iron to breakfast foods (cereals and beverages) and fortification of sugar with vitamin A and fortification of table salt with iodine (Mbaeyi & Onweluzo, 2010). Several studies have shown the enrichment of ogi with different food substances such as bambara groundnut (Mbata, Ikenebomeh, & Alaneme, 2009), pawpaw (Ajanaku et al, 2010), groundnut seed (Ajanaku, Ajanaku, Edobor, & Nwinyi, 2012), soybean (Adeleke & Oyewole, 2010), crayfish (Ajanaku et al, 2013), okra seed meal (Aminigo & Akingbala, 2004), kersting's groundnut (Kerstingiella geocarpah) flour (Aremu, Olaofe, Audu, & Ijalana, 2011), scarlet runner bean (Aremu, Osinfade, Basu, & Ablaku, 2011), cowpea (Ashaye et al, 2000;Oyarekua, 2009), among others.…”
mentioning
confidence: 99%
“…The tannin, phytates and hydrogen cyanide contents were determined as reported by Mbaeyi and Onweluzo [23], while oxalate and saponin were determined using the methods of AOAC [24]. Trypsin inhibitor activity was determined according to the modified method of Kakade et al [25].…”
Section: Determination Of Antinutrientsmentioning
confidence: 99%
“…Malnutrition is becoming an endemic dietary problem in Nigeria [19]. This is characterized by protein-energy malnutrition (PEM) especially among children in the low income family that cannot afford animal protein.…”
Section: Introductionmentioning
confidence: 99%